Analisis Sistem Antrian Model Multiple Channel-Single Phase untuk Mengoptimalkan Efektivitas Pelayanan Teller Bank - Ulfania Liputo; Muhammad Rifai Katili; Djihad Wungguli (Griya Journal of Mathematics Education and Application, 2025)
Queues are commonly encountered in various activities or operations, particularly when available services cannot meet the existing demand. This study aims to analyze the queue system for teller services at Bank Syariah Indonesia (BSI) Gorontalo Branch. The research adopts a quantitative approach, applying the queuing method using the Multiple Channel-Single Phase model. Data analysis was conducted using the "POM-QM for Windows" software. The results indicate that with three tellers, the system’s utility factor reaches 73%, indicating that the tellers are operating very busy. A simulation was then conducted by increasing the number of tellers to four, which resulted in a lower utility value of 55% and a service effectiveness of 37%. This system is still considered efficient, ensuring optimal service performance.